2018
DOI: 10.29011/2638-003x.100007
|View full text |Cite
|
Sign up to set email alerts
|

Post-Dural Puncture Headache - Having No Pillow Does Not Prevent It, Not Even Psychologically. Should We Try Giving Pills Instead?

Abstract: Objectives: To compare patients who received spinal anaesthesia and didn't use pillow in post-op period with those who used pillows and those who mobilised and with those who received general anaesthesia for the development of dural headache, and also neck and back pain. Design: Experimental. Place & Duration of: The study was conducted at the Bone and Joint hospital in Srinagar over a period of 3 months. Study Patients and Methods: This study compared 201 post-op patients who were divided into 4 groups 1. Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The results of our study were consistent with the ndings of the study by Choi and Chang and the study by Shah et alwho found no link between the time of immobilization in the supine position after SA and recurrent PDPH [25,26].…”
Section: Discussionsupporting
confidence: 93%
“…The results of our study were consistent with the ndings of the study by Choi and Chang and the study by Shah et alwho found no link between the time of immobilization in the supine position after SA and recurrent PDPH [25,26].…”
Section: Discussionsupporting
confidence: 93%